COCONUT PRODUCTION IN SEYCHELES - Martin H. Fowler (International Coconut Community, 1988)
This study is based on a description of the Seychelles coconut industry contained in the Central Bank quarterly Review (No. 2, 1983) and on data contained in various pubrications of the Statistics Section on the Information System Division.